Proteinuria and Albuminuria During and After Paricalcitol Treatment in Chronic Kidney Disease Patients. (21st December 2015) - Ekart, Robert; Bevc, Sebastjan; Hojs, Radovan; Hojs, Nina
Abstract: Data on paricalcitol lowering albuminuria and proteinuria already exist; however, it is unclear how paricalcitol withdrawal affects both. Forty‐two nondialysis chronic kidney disease (CKD) patients (29 men) aged 62.3 ± 12 years completed the study. CKD patients with proteinuria and intact parathyroid hormone ≥65 pg/mL received paricalcitol (1 μg/day po) for 6 months. After paricalcitol withdrawal we followed them for 6 more months. Paricalcitol treatment significantly reduced urinary albumin/creatinine ratio (UACR), 24‐hour albuminuria (24hA), and 24‐hour proteinuria (24hP). Six months after drug withdrawal UACR increased significantly, 24hA and 24hP did not change significantly. Serum creatinine and cystatin C significantly increased during treatment, and estimated glomerular filtration rate (eGFR) decreased. After drug withdrawal serum creatinine, cystatin C, and eGFR did not change significantly. In conclusion, 6‐month paricalcitol treatment (1 μg/day) in nondialysis CKD patients significantly reduced albuminuria and proteinuria. Six months after paricalcitol withdrawal 24hA and 24hP did not change significantly. Kidney function decreased during paricalcitol treatment; after paricalcitol withdrawal it remained stable. The unaltered values of 24hA, 24hP, and kidney function after paricalcitol withdrawal could be a delayed effect of paricalcitol treatment.